Post-Enlightenment and Rational-Emotive Therapy (RET): Comments on P.J. Watson's View - Ellis, Albert (The international journal for the psychology of religion, 1993)
Comments on P. J. Watson's (1993) paper, on the post-Enlightenment and rationality, showing how he is correct in many respects but misinterprets the philosophy and practice of rational-emotive therapy.